Two Sides of the Same Coin: Sterile Neutrinos and Dark Radiation, Status and Perspectives - Maria Archidiacono; Stefano Gariazzo (Universe, 2022)
The presence of light sterile neutrinos is one of the unanswered questions of particle physics. The cosmological counterpart is represented by dark radiation, i.e., any form of radiation present in the early Universe besides photons and standard (active) neutrinos. This short review provides a comprehensive overview of the two problems and of their connection. We review the status of neutrino oscillation anomalies, commenting on the most recent oscillation data and their mutual tensions, and we discuss the constraints from other terrestrial probes. We show the shortcomings of translating light sterile neutrinos in cosmology as additional thermalised relativistic species, produced by neutrino oscillations, and we detail alternative solutions, specifically focusing on neutrino nonstandard interactions, and on their link to the Hubble constant problem. The impact of a new force leading to dark radiation–dark matter interactions is also discussed in the realm of new physics in the dark sector.